Peran Notaris dalam Penyelesaian Sengketa Tanah: Pendekatan Hukum dan Praktis - Ana Indrawati (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research explores the role of notaries in resolving land disputes in Indonesia, focusing on both legal and practical approaches. Notaries play a crucial role in providing legal certainty through the drafting of authentic deeds, mediating disputes, and ensuring compliance with agrarian laws and regulations. The study employs a juridical-normative approach utilizing secondary data sources such as laws, regulations, and academic documents. The research aims to identify the legal framework governing notarial duties in land dispute resolution and analyze their practical implications. Key findings underscore the importance of notarial mediation in fostering efficient and fair dispute settlements, thereby contributing to legal stability and societal welfare. The study recommends enhancing notarial oversight, capacity-building in agrarian law and mediation techniques, and fostering collaboration among stakeholders to improve land rights protection and dispute resolution effectiveness